The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.3389/fphar.2022.986683
|View full text |Cite
|
Sign up to set email alerts
|

Advances in lncRNAs from stem cell-derived exosome for the treatment of cardiovascular diseases

Abstract: Cardiovascular diseases (CVDs) are the leading cause of mortality globally. Benefiting from the advantages of early diagnosis and precision medicine, stem cell-based therapies have emerged as promising treatment options for CVDs. However, autologous or allogeneic stem cell transplantation imposes a potential risk of immunological rejection, infusion toxicity, and oncogenesis. Fortunately, exosome can override these limitations. Increasing evidence has demonstrated that long non-coding RNAs (lncRNAs) in exosome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 91 publications
(104 reference statements)
0
6
0
Order By: Relevance
“…Based on the ability to cross the vessel barrier, excellent biocompatibility, and low immunogenicity, exosomes have emerged as efficient nanoscale messengers for cells or cell-tissue communications [ 16 , 29 ]. Mounting evidence suggests that exosomes possess great capacity to deliver protective non-coding RNAs [ 30 , 31 ], miRNAs [ 32 , 33 ], and healthy organelles [ 34 ] for the treatment of ischemic diseases. ASCs are abundant in source, easy to be harvested and modified, and can robustly release exosomes, which would meet huge clinical demands in future [ 18 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the ability to cross the vessel barrier, excellent biocompatibility, and low immunogenicity, exosomes have emerged as efficient nanoscale messengers for cells or cell-tissue communications [ 16 , 29 ]. Mounting evidence suggests that exosomes possess great capacity to deliver protective non-coding RNAs [ 30 , 31 ], miRNAs [ 32 , 33 ], and healthy organelles [ 34 ] for the treatment of ischemic diseases. ASCs are abundant in source, easy to be harvested and modified, and can robustly release exosomes, which would meet huge clinical demands in future [ 18 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Diabetic skin ulcers are characterized by painful ulcers with disintegration of dermis (including epidermis, dermis and, in many cases, subcutaneous tissue) [ 48 ]. At present, the research on the pathology of DFU is mainly focused on immune dysfunction, microbial invasion, impaired cell proliferation, angiogenesis, and pathological scar [ 49 , 50 , 51 , 52 , 53 ]. The molecular and cellular mechanisms in delayed diabetic skin wound healing are shown in Figure 2 .…”
Section: Mechanism Of Delayed Healing Of Diabetic Woundsmentioning
confidence: 99%
“…Therefore, analysis of the major genes involved in glucose and lipid metabolism in zebrafish liver showed that the expression levels of rate-limiting enzyme genes such as cytoplasmic phosphoenolpyruvate carboxykinase (PEP), glucokinase (GK), and pyruvate kinase (PK) in the glycolytic pathway were reduced. Therefore, glucose and pyruvate production were insufficient, resulting in glucose metabolism disorders [94][95][96]. At the same time, alterations in several genes that regulate hepatic lipogenesis, for example, decreased expression of peroxisome proliferator-activated receptor (PPAR) family genes, acetyl-coa carboxylase 1 (ACC1), and fatty acid synthase (FAS) genes, have been associated with downregulation of triglyceride (TG) [97].…”
Section: Toxicological Mechanisms Of Mnps Causing Metabolic Disordersmentioning
confidence: 99%